Elevated LDL-C, high blood pressure, and low peak V̇O2 associate with platelet mitochondria function in children—The Arkansas Active Kids Study - Diaz, Eva C.; Adams, Sean H.; Weber, Judith L.; Cotter, Matthew; Børsheim, Elisabet (Frontiers in molecular biosciences, 2023)
Purpose: To evaluate the association of platelet (PL) mitochondria respiration with markers of cardiovascular health in children ages 7–10 years. Methods: PL mitochondrial respiration (n = 91) was assessed by high resolution respirometry (HRR): Routine (R) respiration, complex (C) I linked respiration (CI), and maximal uncoupled electron transport capacity of CII (CII E ) were measured. The respiratory control ratio (RCR) was calculated as the ratio of maximal oxidative phosphorylation capacity of CI and CI leak respiration (P CI /L CI ). Peak V . O 2 (incremental bike test) and body composition (dual-energy X-ray absorptiometry) were measured. Multiple generalized linear regression analysis was used to model the association of measures by HRR with variables of interest: adiposity, low-density lipoprotein (LDL-C) and triglyceride (TG) status (normal vs. elevated) HOMA2-IR, blood pressure status (normal vs. high), and demographics. Results: R and CI-linked respiration positively associated with adiposity, high blood pressure (HBP), and peak V . O 2 . R and CI-linked respiration had inverse association with age and elevated LDL-C. CII E was higher in children with elevated LDL-C (log-β = −0.54, p = 0.010). HBP and peak V . O 2 interacted in relation to RCR (log-β = −0.01, p = 0.028). Specifically, RCR was lowest among children with HBP and low aerobic capacity (i.e., mean peak V . O 2 -1SD). HOMA2-IR did not associate with measures of PL mitochondria respiration. Conclusion: In PL, R and CI-linked mitochondrial respiration directly associate with adiposity, peak V . O 2 and HBP. Elevated LDL-C associates with lower CI-linked respiration which is compensated by increasing CII respiration. PL bioenergetics phenotypes in children associate with whole-body metabolic health status.